Efficacy and Safety of Tofacitinib in Ulcerative Colitis Based on Prior Tumor Necrosis Factor Inhibitor Failure Status - William J. Sandborn; Laurent Peyrin–Biroulet; Ala I. Sharara; Chinyu Su; Irene Modesto; Rajiv Mundayat; Levent Mert Günay; Leonardo Salese; Bruce E. Sands (2021)
Tofacitinib is an oral, small-molecule Janus kinase inhibitor for the treatment of ulcerative colitis (UC). We summarize the efficacy and safety data of tofacitinib 5 or 10 mg twice daily in the UC clinical program, stratified by prior tumor necrosis factor inhibitor (TNFi) failure status.Efficacy was assessed in the pooled phase 3 OCTAVE Induction 1 and 2 studies (N = 1139), the phase 3 OCTAVE Sustain maintenance study (N = 593), and the dose-escalation subpopulation of the open-label, long-term extension OCTAVE Open study (N = 59). Safety was assessed in OCTAVE Sustain, the dose-escalation subpopulation, and the Overall Cohort, which included patients from OCTAVE Induction 1 and 2, OCTAVE Sustain, and OCTAVE Open (N = 1124; no prior TNFi failure N = 541; prior TNFi failure N = 583; phase 2 data were excluded when stratified by prior TNFi failure status). The dose-escalation subpopulation received tofacitinib 10 mg twice daily in OCTAVE Induction 1 and 2, tofacitinib 5 mg twice daily in OCTAVE Sustain, and tofacitinib 10 mg twice daily in OCTAVE Open.Tofacitinib had greater efficacy than placebo, regardless of prior TNFi failure status. In OCTAVE Sustain and the Overall Cohort, herpes zoster [HZ] (nonserious and serious) rates were numerically higher in tofacitinib-treated patients with vs without prior TNFi failure. Dose escalation to tofacitinib 10 mg twice daily generally recaptured clinical response for most patients. HZ (nonserious and serious) rates were numerically higher in the dose-escalation subpopulation vs the Overall Cohort.Tofacitinib was efficacious in patients with UC regardless of prior TNFi failure status. HZ (nonserious and serious) rates were numerically higher in patients who had previously failed TNFi. ClinicalTrials.gov: A3921063 (NCT00787202); OCTAVE Induction 1 (NCT01465763); OCTAVE Induction 2 (NCT01458951); OCTAVE Sustain (NCT01458574); and OCTAVE Open (NCT01470612).